Identifying neutrophil-associated subtypes in ulcerative colitis and confirming neutrophils promote colitis-associated colorectal cancer - Zhang, Chen; Zhang, Jiantao; Zhang, Yanli; Song, Zian; Bian, Jing; Yi, Huanfa; Ma, Zhanchuan (Frontiers in Immunology, 2023)
Ulcerative colitis (UC) is a chronic inflammatory disease of the intestinal mucosa, the incidence of which has increased worldwide. There is still a lack of clear understanding of the pathogenesis of ulcerative colitis that ultimately leads to colitis-associated colorectal cancer. We identified 65 differentially expressed genes in UC samples and healthy controls. GSEA, KEGG, and GO analyses displayed that DEGs were enriched in immune-related pathways. CIBERSORT analysis revealed increased infiltration of neutrophils in UC tissues. The red module, obtained by WGCNA analysis, was considered to be the most relevant module for neutrophils. Based on neutrophil-associated differentially expressed genes, UC patients were classified into two subtypes of neutrophil infiltration. We discovered that the highly neutrophil-infiltrated subtype B of UC patients had a higher risk of developing CAC. Five genes were identified as biomarkers by searching for DEGs between distinct subtypes. Finally, using the mouse model, we determined the expression of these five genes in the control, DSS, and AOM/DSS groups. The degree of neutrophil infiltration in mice and the percentage of MPO and pSTAT3 expression in neutrophils were analyzed by flow cytometry. In the AOM/DSS model, MPO and pSTAT3 expressions were significantly increased. These findings suggested neutrophils might promote the conversion of UC into CAC. These findings improve our understanding of the pathogenesis of CAC and provide new and more effective insights into the prevention and treatment of CAC.